Analysis of Reliability of A Two-Non-Identical Units Cold Standby Repairable System Has Two Types of Failure - Gupta, Praveen; Vinodiya, Pooja (International Journal of Computer Sciences and Engineering, 2025)
This paper shows the analysis of reliability of a system composed of the two- N.I.U., NO and NS in which NO is operative and NS is kept in standby mode upon failure of operative units NO units NS become operative instantaneously. Unit-1 has two types of failures. Let failure time distribution of type 1 and type 2 are assumed to be exponential with parameters λ1 and λ2 respectively, and the repair time is taken as general. When the second unit is failed it goes for replacement.